Association of Early Increase in Body Temperature with Symptomatic Intracranial Hemorrhage and Unfavorable Outcome Following Endovascular Therapy in Patients with Large Vessel Occlusion Stroke - Yimin Chen; Thanh N. Nguyen; Mohammad Mofatteh; Mohamad Abdalkader; Jack Wellington; Zile Yan; Jiale Wu; Wenjun Liang; Gan Chen; Daiyu Liang; Junxian Lin; Baoxin Chen; et al. (Journal of Integrative Neuroscience, 2022)
Introduction: The aim of this study was to investigate for possible associations between an early increase in body temperature within 24 hours of endovascular therapy (EVT) for large vessel occlusion stroke and the presence of symptomatic intracranial hemorrhage (sICH) and other clinical outcomes. Methods: This was a retrospective study of consecutive patients with large vessel occlusion stroke who were treated with EVT from August 2018 to June 2021. Patients were divided into two groups based on the presence of fever, as defined by a Peak Body Temperature (PBT) of ≥37.3 °C. The presence of sICH and other clinical outcomes were compared between the two groups. Results: The median NIHSS admission score (IQR) was 16.0 (12.0, 21.0), with higher NIHSS scores in the PBT ≥37.3 °C group than in the PBT <37.3 °C group (18 vs 14, respectively; p = 0.002). There were no differences in clinical outcomes at 3 months between patients with PBT <37.3 °C and patients with PBT between 37.3 °C and 38 °C. However, patients with PBT ≥38 °C had an increased risk of sICH (adjusted odds ratio (OR) = 8.8, 95% confidence interval (95% CI): 1.7–46.0; p = 0.01), increased inpatient death or hospice discharge (OR = 10.5, 95% CI: 2.0–53.9; p = 0.005), poorer clinical outcome (OR = 25.6, 95% CI: 5.2–126.8; p < 0.001), and increased 3-month mortality (OR = 6.6, 95% CI: 1.8–24.6; p = 0.01). Conclusions: Elevated PBT (≥38 °C) within 24 hours of EVT was significantly associated with an increased incidence of symptomatic intracranial hemorrhage, discharge to hospice or inpatient death, poorer clinical outcome and 3-month mortality, and with less functional independence. Further large-scale, prospective and multicenter trials are needed to confirm these findings.